ANALISIS YURIDIS PERBUATAN PENYUAPAN DALAM TINDAK PIDANA KORUPSI (Studi Putusan Nomor 10/ Pid Sus-Tpk /2021/PT DKI) - Erawati C. Lbn Tobing; Davit Rahmadan; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Corruption has become a common habit in Indonesian society, especially amongofficials and state administrators in the Republic of Idonesia. As in this case the state civilapparatus being caught in a criminal case of bribery in corruption in 2021. With their statusas a state civil apparatus, including the law enforcement profession, it should receive moresevere criminal sanctions. In reality, the crime in decision case Number 10 Pid Tpk 2021/PTDKI was actually without any weight. Apart from that, the judge’s considerations regardinggender status where the perpetrator was a woman led to considerations that made thingseasier for the perpetrator.This research aims first, to analyze the judge’s considerations regarding criminalacts of corruption in decision Number 10/Pid Sus-Tpk/2021/PT DKI based on a progressivelegal perspective. Second, to find out whether the application of criminal sanctions fordefendants of corruption in decision Number 10/Pid Sus-Tpk/2021/PT DKI is in accordancewith article 5 of the judicial power law.In this paper using normative legal research methods, namely library law research.In connection with the type of research used, namely normative research, the approach usedis a case approach and a statutory approach. Analysis was carried out on library materialsor secondary data consisting of primary legal materials and tertiary legal materials, theresult of the analysis are then described in qualitative descptive manner.The results of the study indicate that in both the juridical and non-juridicalconsiderations above, the writer considers that the basis of the judge's legal consideration isnot under the principle of equality before the law, and did not consider the status of theaccused as a law enforcement officials but instead committed a criminal act of corruption.In the concept of progressive law, judges can be more flexible in giving decisions, namely bymaking discoveries or breakthroughs related to what is currently irrelevant. However, in theimplementation of the criminal sanction against Attorney Pinangki in Decision Number10/Pis.SusTPK/2021/PT DKI if viewed based on a progressive law perspective it has notbeen fulfilled.Keywords :Criminal Acts Of Corupption, Penalty, Judge’s Consideration.